Resor Pemandian Air Panas Di Desa Pawan Rokan Hulu Dengan Pendekatan Arsitektur Hijau - Izazul Lizar; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Rokan Hulu regency has so many attractions, including the nature attractions and the religion attractions. One of the nature attractions in Rokan Hulu is the hot spring in Pawan village. But, the condition is so concern because its not maintained well by the society and government. Therefore, the hot spring in Pawan village has re-designed with the new concept to increased the tourism destinations in Riau province, especially in Rokan Hulu. The Hotspring Resort is good alternative object for the hot spring in Pawan village, with tje natural view that support to the resort. One of them, Bukit Suligi, Bukit Barisan view. The design of the Hotspring Resort is forwading the green architecture principle. The aim is to design the building that minimalize negative effect to the environment, nature and human being. So that will build up the better and healthier place. Moreover, the concept of the design is "back to nature" which bring up the harmony between the building and environment. Then, supported by applying the green architecture design strategy of Alison G Kwok, AIA and Walter T, Grondzik PE, which is: (1) Envilope related to envilopment, (2) Lightning related to exposure, (3) Cooling related to refrigerant, (4) Energy Product related to energy production, (5) Water and waste related to water utilization. Finally, the Hotspring Resort will be design of tourism destination which forward the harmonization between the building and environment behind. The design has 4 hectare land area and 24578,304 m² land building.Keywords: The Hotspring Resort. Green Architecture. Back To Nature. The Strategy Design by Alison G. Kwok.